Corticosteroids for Acute and Recurrent Idiopathic Pericarditis: Unexpected Evidences - Antonio Perrone; Anna Castrovilli; Giuseppina Piazzolla; Sabina Savino; Alessia D’Introno; Carlo Sabbà (Cardiology Research and Practice)
Pericarditis is a common disease, often postviral or “idiopathic,” diagnosed in about 5% of emergency room visits for non-ischemic chest pain. Although pericarditis often occurs as a benign and self-limiting disease, it may present recurrences. The first-line therapy includes aspirin/nonsteroidal anti-inflammatory drugs (ASA/NSAIDs) plus colchicine. Steroids especially at high-dose have been associated with a higher recurrence rate. In this retrospective study, we evaluated efficacy and safety of ASA/NSAIDs and prednisone in the treatment of acute or recurrent idiopathic pericarditis (colchicine was off-label in the period of the study). The cohort included 276 patients diagnosed with acute idiopathic pericarditis. Mean age was 45.4 ± 12.7 years, and males were significantly higher in number and younger than females. Sixty-one patients (22.1%) were treated with prednisone and 215 with ASA/NSAIDs (77.9%). 171 patients experienced at least one recurrence (62%). No difference in recurrence rate was observed (p=0.257) between the groups treated with prednisone (55.7%) vs. ASA/NSAIDs (63.7%). The recurrences were treated with steroids at low doses and very gradual tapering, and the dose reduction was slower as the number of relapses was higher. Steroids alone were administered to about 80% of patients, while in the remaining 20% of cases, they were associated with ASA/NSDAIDs or colchicine. Approximately 90% of patients had a very favorable course, that is no more than 2 relapses and no patients presented serious side effects. Steroids at low dose, did not act, surprisingly, as an independent risk factor for recurrences and therefore may be considered a successful and safe treatment for acute and recurrent idiopathic pericarditis.